Spread of internet rumours and ways of handling spread of internet rumours during Covid-19 pandemic: a study of unviersity students in Klang Valley - Hii, Evangeline Wen Qi (2024)
This research investigates the spread and management of internet rumours during the COVID19 pandemics. The spreading of internet rumours has not been something new in this globalized era and yet has become an ordinary craze among the readers especially in our country, Malaysia. With the hit of COVID-19 in 2019, various unverified news and rumours are served before our eyes. These ruinous actions will eventually distress the community, economic growth, and national security. Therefore, the ways of the users handle internet rumours should also be considered. This study takes a quantitative approach, analysing the relationship between the cause of the spread of rumours on COVID-19 and the ways in handling Internet rumours by the users when facing Internet rumours. The initial finding indicates that information on the Internet is easier to acquire, and easily relied on by the reader in whatever they read, and selfsatisfaction is the primary reason for an individual who inclines intending to spread fake news. The research aims to provide insight into how influential the management of the consumers in fighting against Internet rumours during the pandemic period is.